A New Indicator Based on Neftçi's Approach for Predicting Turning Points of the Euro-Zone Growth Cycle - Jacques Anas; Muriel Nguiffo-Boyom (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
[...] in many situations a decision does not have to be made immediately, but can be delayed until additional information has been acquired. Sequential analysis seems particularly applicable to the problem of predicting turning points in the business cycle (Palash and Radecki, 1985). Elaborating on this idea, we propose a new approach to predict cyclical turning points in the Euro-zone using the Neftçi's approach. The output is a probability index for a forthcoming economic turning point. – – Der Aufsatz greift die Idee auf, dass in vielen Situationen Entscheidungen nicht sofort getroffen werden müssen, sondern verschoben werden, bis zusätzliche Informationen zur Verfügung stehen. Sequentielle Analysemethoden scheinen daher für das Problem der Wendepunktanalyse besonders geeignet zu sein. Hierfür wird auf den Ansatz von Neftçi zurückgreifend ein Wahrscheinlichkeitsindikator für künfige Wendepunkte des europäischen Konjunkturzyklus vorgestellt.
Keywords: 330; Konjunktur; Konjunkturindikator; Eurozone; Schätzung; EU-Staaten